Knowledge, Attitude, and Psychological Impacts of COVID-19 in Saudi Arabia - Naif Alanazi; Khaled Bahjri (Frontiers Media S.A., 2022)
BackgroundThe world has been facing an unprecedented pandemic of COVID-19 with over 336 million people infected and millions of deaths. This required an enormous communication effort response from governments, international, and individuals to keep the public informed about the outbreak. When a pandemic affects communities, individuals' knowledge and attitude are important factors to contain the outbreak. Thus, the purpose of this study is to measure individuals' knowledge and attitude toward COVID-19 and ascertain whether a need exists for mental health services for those who were affected by the pandemic.MethodsA cross-sectional design was used to measure the knowledge, attitude, and psychological impacts about the COVID-19 pandemic among the Saudi population. Research participants were recruited using a snowball sampling technique through the social media platform WhatsApp. A total of 482 eligible individuals participated from various locations in Saudi Arabia represented almost all Saudi regions. The questionnaire consisted of seven questions evaluating knowledge, seven gauging attitudes, and 16 questions assessing anxiety and perceived need for mental healthcare services.ResultsA modest level of knowledge (59%) was found among the Saudi population sampled about the COVID-19 pandemic, and satisfactory knowledge (>80%) about its preventive measures. Anxiety and stress existed among the participants (79% obsessed with COVID-19), with an 88% approval rate for obtaining mental health services for individuals highly affected by the pandemic.ConclusionThere is a need to increase awareness and provide continuous updates regarding the pandemic situation. Promoting access to mental health services is critical, as well as finding creative and suitable strategies to deliver mental health services to those who need them.